Pendampingan Mahasiswa Kampus Mengajar sebagai Implementasi Merdeka Belajar Kampus Merdeka di SD Negeri - Septi Dariyatul Aini; Yuliarsih Yuliarsih; Laili Amalia (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This community service is carried out to help teachers and schools, especially in improving numeracy literacy and the use of technology in the learning process. One form of community service that is carried out is through mentoring in the Kampus Mengajar program which is one of the eight superior programs offered by the Minister of Education and Culture. The mentoring referred to here is mentoring students who have passed the selection for the teaching program at school as Field Mentor Lecturers for the Kampus Mengajar program. Lecturers guide 3-4 students from several state and private campuses domiciled in Pamekasan or Sumenep and are placed at SDN Kowel 1 Pamekasan, SDN Groom Pamekasan and SDN Batuan 1 Sumenep. This mentoring has a direct impact on both the school including teachers, students, principals and of course students. For students, it is able to improve numeracy and literacy. For teachers, it increases knowledge related to technology and for students, it increases experience in teaching at school and how to collaborate with teachers. For schools, it helps with management and administration.